2020
DOI: 10.1371/journal.pntd.0008608
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Signaling Lymphocytic Activation Molecule Family 1 (SLAMF1) receptor with Trypanosoma cruzi is strain-dependent and affects NADPH oxidase expression and activity

Abstract: The receptor Signaling Lymphocyte-Activation Molecule Family 1 (SLAMF1) controls susceptibility to Infection by the lethal Trypanosoma cruzi Y strain. To elucidate whether genetic diversity of the parasite was related with disease susceptibility, we further analyzed the role of SLAMF1 using 6 different Trypanosoma cruzi strains including Y. The interaction of SLAMF1 receptor with T. cruzi was evidenced by fluorescence microscopy, flow cytometry and quantitative PCR. All the strains, except VFRA, showed a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Histological data, in concordance with the previous report from our group [27], showed a moderate auricular inflammatory reaction with Y strain infection (Figure 5). Although no evidence of the infection is shown here, parasite load was quantified in the same cardiac samples in a previously published manuscript [28], indicating cardiac parasitization. The right atrial cell population was evaluated on this occasion with more detail, suggesting nodal-like cell depopulation.…”
Section: Discussionmentioning
confidence: 47%
“…Histological data, in concordance with the previous report from our group [27], showed a moderate auricular inflammatory reaction with Y strain infection (Figure 5). Although no evidence of the infection is shown here, parasite load was quantified in the same cardiac samples in a previously published manuscript [28], indicating cardiac parasitization. The right atrial cell population was evaluated on this occasion with more detail, suggesting nodal-like cell depopulation.…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, Slamf1-defIcient myeloid cells are impaired in their ability to replicate the parasite, and they display an altered pattern of cytokine production. Recent studies by Poveda et al [ 27 ] have shown that the interaction of SLAMF1 with T. cruzi is strain-dependent and affects NOX2 expression and ROS production, since five out of six strains tested showed a decrease in parasite load in Slamf1 −/− infected macrophages compared to wild-type macrophages. Also, NOX2 expression and ROS production were increased in Slamf1 −/− infected macrophages when compared to wild-type macrophages [ 27 ].…”
Section: Inflammation and Oxidative Damage In Chagas Diseasementioning
confidence: 99%
“…In addition, Slamf1 -/macrophages became more resistant to the infection with the same strain. More recently, we described increased resistance of Slamf1 -/macrophages to the infection with other parasite strains (Dm28c, M6421, 10R26, and Bug2148) except for one (VFRA) (Poveda et al, 2020). This correlated with the increased expression of NOX-2 expression and ROS production in Slamf1 -/macrophages infected with all the strains except VFRA in comparison to the WT.…”
Section: Role Of Slamf1 Receptor On Ros Generation and Mdsc Expansion During Trypanosoma Cruzi Infectionmentioning
confidence: 66%
“…These opposing strain-dependent roles of SLAMF1 in infectivity and ROS production may explain some of the mentioned discrepancies in the chapter above about the role of ROS in T. cruzi infection. Moreover, Slamf1 -/mice infected with the Y strain showed a shift from MDSC expansion to M1 polarization compared to the WT (Poveda et al, 2020), suggesting that SLAMF1 may have a role in emergency myelopoiesis and possibly mediating MDSCs expansion, a possibility that should be explored in the future.…”
Section: Role Of Slamf1 Receptor On Ros Generation and Mdsc Expansion During Trypanosoma Cruzi Infectionmentioning
confidence: 99%